In Their Own Words: Women Veterans Identify the Personal Consequences of Military Sexual Trauma Victimization - Reinhardt, Kristen M. (Violence against women, 2024)
This qualitative study provides a platform for women veterans to inform our perspective of their experienced impacts following military sexual trauma (MST). We engaged 23 women veterans in semistructured interviews and used a grounded theory-informed thematic analytic approach, to interpret women's experiences. Women described negative impacts of their MST experiences across psychological, behavioral, and occupational domains. Less frequently, women discussed experiences of posttraumatic growth. These results aid our understanding of the complexities of women's posttrauma experiences and suggest that holistic intervention frameworks focused on a range of potential intervention targets are warranted in helping women veterans recover from MST.